Migraine in menopausal women: a systematic review - Ripa P; Ornello R; Degan D; Tiseo C; Stewart J; Pistoia F; Carolei A; Sacco S (Dove Medical Press, 2015)
Patrizia Ripa,1 Raffaele Ornello,1 Diana Degan,1 Cindy Tiseo,1 Janet Stewart,2 Francesca Pistoia,1 Antonio Carolei,1 Simona Sacco1 1Department of Applied Clinical Sciences and Biotechnology, Institute of Neurology, University of L’Aquila, L’Aquila, Italy; 2Psychology Division, School of Natural Sciences, University of Stirling, Scotland, UK Abstract: Evidence suggests that migraine activity is influenced by hormonal factors, and particularly by estrogen levels, but relatively few studies have investigated the prevalence and characteristics of migraine according to the menopausal status. Overall, population-based studies have shown an improvement of migraine after menopause, with a possible increase in perimenopause. On the contrary, the studies performed on patients referring to headache centers have shown no improvement or even worsening of migraine. Menopause etiology may play a role in migraine evolution during the menopausal period, with migraine improvement more likely occurring after spontaneous rather than after surgical menopause. Postmenopausal hormone replacement therapy has been found to be associated with migraine worsening in observational population-based studies. The effects of several therapeutic regimens on migraine has also been investigated, leading to nonconclusive results. To date, no specific preventive measures are recommended for menopausal women with migraine. There is a need for further research in order to clarify the relationship between migraine and hormonal changes in women, and to quantify the real burden of migraine after the menopause. Hormonal manipulation for the treatment of refractory postmenopausal migraine is still a matter of debate. Keywords: headache, female, menstrual cycle, sex hormones